Managing Collaborative Matching Fund Kemendikbud: Studi Pada Program Kedaireka Universitas Negeri Makassar - Nurharsya Khaer Hanafie; Syamsul Bahri; Novayanti Novayanti; Ahmad Fudail (Universitas Negeri Makassar, 2022)
Abstrak. This research was carried out at Makassar State University, focusing on Management Collaboration in the UNM Matching Fun program with the Industrial and Business World. This study will analyze the Effectiveness of Managing Collaboration in the kedaireka Collaboration program. All data or materials used to support the research to be carried out cover every aspect related to the research problem. This study aims to analyze the Managing Collaboration in the Kedaireka Collaboration program at Makassar State University. This research understands the phenomena originating from the implementation of the Collaboration program. Therefore, the researcher chose to use a qualitative approach with descriptive analysis methods, with the consideration that a qualitative approach is a research procedure that seeks to describe the views, perceptions of the researcher as a whole related to the data obtained in the field. Researchers are more dominant in conducting qualitative research in the nature of case studies with the aim of obtaining a more authentic understanding of the collaboration program, namely the Kedaireka program. In addition, qualitative case study research understands phenomena from the participant's point of view, the social and institutional context, which are considered to be very suitable for the problem to be studied. The results of his research indicated that the Kedaireka mutching fun program was running effectively and was able to provide a space for collaboration for Makassar State University lecturersKeywords: Managing Collaboration, Kedaireka, Matching Fund